2006
DOI: 10.1159/000092896
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Pictorial Representation of Illness and Self Measure in Individuals with Alcohol Dependence, Alcohol Abuse or At-Risk Drinking

Abstract: Background: The impact of chronic illnesses is not only influenced by one’s physical functioning but also by its subjective importance to the individual’s life. However, it is often difficult to asses such an impact in an appropriate way. PRISM (pictorial representation of illness and self measure) measures the perception of illness and first data on its validity have been published. The aim of the present study was to prove the applicability of PRISM regarding alcohol-dependent patients. Therefore, a comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 43 publications
(26 reference statements)
0
13
0
Order By: Relevance
“…Support for this hypothesis further comes from the comments of the patients, who frequently referred to (the success of) their own coping efforts (e.g., "I make sure my diabetes does not become too big an issue in my life"). In a previous study among individuals with problematic alcohol use, Reinhardt et al [ 13 ] also found SIS to discriminate between different levels of readiness to change, which also reflects coping efforts. SIS was partly predicted by age, indicating older people on average having higher SIS scores.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Support for this hypothesis further comes from the comments of the patients, who frequently referred to (the success of) their own coping efforts (e.g., "I make sure my diabetes does not become too big an issue in my life"). In a previous study among individuals with problematic alcohol use, Reinhardt et al [ 13 ] also found SIS to discriminate between different levels of readiness to change, which also reflects coping efforts. SIS was partly predicted by age, indicating older people on average having higher SIS scores.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, studies in patients with rheumatoid arthritis [ 6 ], chronic obstructive pulmonary disease [ 7 ], systemic lupus erythematosus [ 8 ], psoriasis [ 9 ], vitiligo [ 10 ], and chronic pain [ 11 ] have provided evidence suggesting that PRISM measures aspects of suffering, and a validation study with over 700 patients from different disease groups showed PRISM to have good test-retest reliability, and to be sensitive to therapeutic change [ 12 ]. In addition, the PRISM has been found useful in differentiating alcohol-related disorders [ 13 ], and in assessing post-traumatic growth in bereaved parents [ 14 ]. Because the measure is generic, it allows for comparison of suffering not only across different diseases, but even including problems of a different nature.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of interpretation, two SIS ranges were distinguished (a mark within the self-circle, and a mark outside the self-circle) [ 26 ]. Previous studies have identified no disadvantages of the paper and pencil versus the original version, which uses a disc instead of a pencil mark [ 23 , 43 , 44 ]. The test and its instructions are shown in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…It is assumed that the regular association of these cues with the ingestion of alcohol leads to conditioned reactions [1, 2], motivating reward or relief craving and instigating drug intake [3]. In addition, the occurrence of these conditioned reactions may be interpreted by the individual as sign of intrusiveness and uncontrollability of the illness [4] and thus contribute to low self-efficacy. This stresses the necessity of interventions aiming at reducing conditioned reactions (i.e.…”
Section: Introductionmentioning
confidence: 99%